The Fourth crusade : event, aftermath, and perceptions : papers from the Sixth Conference of the Society for the Study of the Crusades and the Latin East, Istanbul, Turkey, 25-29 August 2004 /: event, aftermath, and perceptions : papers from the Sixth Conference of the Society for the Study of the Crusades and the Latin East, Istanbul, Turkey, 25-29 August 2004. (2016) - Unknown
No abstract available